Oral cancer in India, a growing problem: Is limiting the exposure to avoidable risk factors the only way to reduce the disease burden?. (February 2022) - Subash, Anand; Bylapudi, BhanuPrakash; Thakur, Shalini; Rao, Vishal U.S.
Abstract: Cancer represents an uncontrolled growth of cells that invade and cause damage to the adjacent tissues. Globally oral cancer ranks as the sixth most common type of cancer. As compared to the west, the problem of oral cancer is significantly higher in India. The spectrum of oral diseases is formed with oral cancer at one extreme and potentially malignant disorders (PMDs) at the other extreme. Screening programs for the early detection and prevention of oral cancer indicate that visual examination as a part of a population-based screening program reduces the mortality rate of oral cancer in high-risk individuals. Tobacco and alcohol consumption remains the main factors for oral cancer and education of the population about the ill effects of tobacco and alcohol consumption is necessary at a broader scale.